Knee Arthroscopy - McKeon, Brian P.; Bono, James V.; Richmond, John C. (Springer New York : Imprint: Springer, 2009)
Arthroscopic procedures are a welcome alternative to total joint replacement and, with millions of procedures performed each year, the field of knee arthroscopy is rapidly advancing as instrumentation and applications are developed and refined. Knee Arthroscopy is a technique-oriented "how-to" guide, written by internationally renowned authorities who present the latest advances in the field in a clear, step-by-step format. Chapters discuss issues such as meniscal transplantation, articular cartilage repair, anterior cruciate ligament treatment and other surgical procedures, and the text is supplemented throughout by case studies, clinical pearls and a wealth of illustrations. Knee Arthroscopy is a comprehensive reference sure to be invaluable for anyone involved in care of the knee, from the general orthopedist to the most skilled knee surgeon.